Aerobic Lineage of the Oxidative Stress Response Protein Rubrerythrin Emerged in an Ancient Microaerobic, (Hyper)Thermophilic Environment - Cardenas, Juan P.; Quatrini, Raquel; Holmes, David S. (Frontiers in Microbiology, 2016)
Rubrerythrins (RBRs) are non-heme di-iron proteins belonging to the ferritin-like superfamily (FLSF). They are involved in oxidative stress defense as peroxide scavengers in a wide range of organisms. The vast majority of RBRs, including classical forms of this protein, contain a C-terminal rubredoxin-like domain involved in electron transport that is used during catalysis in anaerobic conditions. Rubredoxin is an ancient and large protein family of short length (<100 residues) that contains a Fe-S center involved in electron transfer. However, functional forms of the enzyme lacking the rubredoxin-like domain have been reported (e.g., sulerythrin and ferriperoxin). In this study, phylogenomic evidence is presented that suggests that a complete lineage of rubrerythrins, lacking the rubredoxin-like domain, arose in an ancient microaerobic and (hyper)thermophilic environments in the ancestors of the Archaea Thermoproteales and Sulfolobales. This lineage (termed the “aerobic-type” lineage) subsequently evolved to become adapted to environments with progressively lower temperatures and higher oxygen concentrations via the acquisition of two co-localized genes, termed DUF3501 and RFO, encoding a conserved protein of unknown function and a predicted Fe-S oxidoreductase respectively. Proposed Horizontal Gene Transfer (HGT) events from these archaeal ancestors to Bacteria expanded the opportunities for further evolution of this RBR including adaption to lower temperatures. The second lineage (termed the cyanobacterial lineage) is proposed to have evolved in cyanobacterial ancestors, maybe in direct response to the production of oxygen via oxygenic photosynthesis during the Great Oxygen Event (GOE). It is hypothesized that both lineages of RBR emerged in a largely anaerobic world with “whiffs” of oxygen and that their subsequent independent evolutionary trajectories allowed microorganisms to transition from this anaerobic world to an aerobic one.